2009
DOI: 10.1177/0885328208100667
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Repairing of Intestinal Fistula Using chitosan hydrogel

Abstract: Intestinal fistula is associated with high morbidity and difficult to manage. Many fistulas require surgical treatment, which usually consists of segmental resection. In this study, using a rat model, the effectiveness of chitosan hydrogel as an intestinal fistula repair agent was investigated. Twenty rats underwent laparotomy under general anesthesia. The antimesentric portion of the cecum was incised (1 cm) and sutured to the abdominal wall. Chitosan hydrogel was applied daily to the fistula until it was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A model recapitulating the pathogenesis of intestinal fistula does not exist. Rat models in which fistula are surgically created have been used to assess repair agents such as chitosan hydrogel, 49 stable gastric pentadecapeptide BPC 157 50 or stem cell therapy. 51 Unfortunately, these models are not suitable for testing agents having the potential to control cellular and molecular processes leading to fistula development as those are bypassed in the surgical models.…”
Section: Discussionmentioning
confidence: 99%
“…A model recapitulating the pathogenesis of intestinal fistula does not exist. Rat models in which fistula are surgically created have been used to assess repair agents such as chitosan hydrogel, 49 stable gastric pentadecapeptide BPC 157 50 or stem cell therapy. 51 Unfortunately, these models are not suitable for testing agents having the potential to control cellular and molecular processes leading to fistula development as those are bypassed in the surgical models.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbani et al used an innovative approach to repair intestinal fistulas using chitosan hydrogels. The study revealed that the wound healing as well as antibacterial properties of chitosan hydrogel was very effective in healing cecal fistulas in rats [134]. Falabella et al demonstrated the efficacy of in situ-crosslinked oxidized dextran/N-carboxyethyl chitosan hydrogel in reducing intra-abdominal adhesion in rats by forming a physical barrier between the injured areas [135].…”
Section: Intestinal Regenerative Engineeringmentioning
confidence: 99%
“…Some of these properties are often present in hydrogels, three-dimensional polymeric structures able to entrap large amount of water, which upon an appropriate design can be injectable, forming in situ a tissue mimicking matrix. For example, the use of a chitosan based hydrogel has been reported to promote the healing of intestinal fistula in a rat model; however daily applications of the material were necessary [ 11 ]. In a clinical study, Krause et al.…”
Section: Introductionmentioning
confidence: 99%